MANAGEMENT OF COATED TONGUE RESEMBLES PSEUDOMEMBRANOUS CANDIDIASIS IN A MULTIDRUG-THERAPY PATIENT - Astrid Widhowaty Santoso; Agustin Ninintowe T. Santo; Riani Setiadhi (FKG ULM, 2024)
Introduction: Coated tongue or tongue coating is characterized by white deposit covering dorsum of the tongue. The thick-coated tongue almost resembles oral candidiasis. It is challenging to make the diagnosis and provide the proper treatment especially when supporting examination tools are unavailable. Objective: To discuss the diagnosis making and management of coated tongue with suspicion of pseudomembranous candidiasis with a lack of supporting examination tools. Case(s): A 61-year-old man was referred to the Oral Medicine Clinic for oral examination. No complaints of pain in the oral cavity. He had a history of type-2 diabetes mellitus, coronary heart disease (CHD), and pleuritis and was taking medication. During hospitalization, never cleaned his oral cavity. Case Management: Intraorally, white plaque covering almost the entire dorsum of the tongue, which could be scraped off on the anterior 1/3 but not on the posterior 2/3. The diagnosis was suspected coated tongue with oral candidiasis as the differential diagnosis. The treatments were compressing the tongue using gauze soaked in 3% hydrogen peroxide (H2O2) solution, scrapping off using a tongue scraper, then rinsing with water. The thick-coated tongue can be easily removed. He was also given 0,2% chlorhexidine gluconate (CHX) mouthwash as an antiseptic and petroleum jelly for dry lips. The tongue condition improved on 2nd day therapy after rinsing regularly using 0,2% CHX. Conclusion: Recognizing the signs, symptoms, and associated factors of Candida infection is important. Coated tongue which resembles pseudomembranous candidiasis was successfully treated using 3% H2O2 compresses, tongue scraping, and 0.2% CHX mouthwash. Keywords: Chlorhexidine gluconate, Coated tongue, Hydrogen peroxide, Infection, Oral candidiasis